HUBUNGAN PENGETAHUAN IBU TENTANG RAMPAN KARIES PADA ANAK BALITA DI TK ISLAM TERAPAN BAITUSSHALIHIN KECAMATAN ULEE KARENG KOTA BANDA ACEH - Zahara, Elfi; Sari, Ade Yosita (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2022)
Rampant caries is a multifactorial disease that interacts with, among others, from food and habits that are not in accordance with health such as eating food and feeding through bottles. The results of interviews conducted by researchers on 10 mothers of Applied Islamic Kindergarten Baitussahalihin that 8 students' mothers still lacked knowledge about rampant caries in children. The results of the examination conducted by researchers on 7 out of 10 students (70%) had tooth decay (rampan caries). The purpose of this study was to determine the relationship between mother's knowledge about rampant caries in children under five at Baitusshalihihin Applied Islamic Kindergarten, Ulee Kareng District, Banda Aceh City. This type of research is analytic with cross sectional study method and using a questionnaire as an instrument. The sampling technique in this study used a total sampling technique, because all the population was used as a sample consisting of 40 students and 40 mothers as respondents to be used as samples. The results showed that the frequency distribution of maternal knowledge about rampant caries was in the poor category 54.2%. The results of the chi square statistical test showed that there was a significant relationship between the mother's knowledge of rampant caries and the p value = 0.006 (p < 0.05). It can be concluded that there is a relationship between mother's knowledge about rampant caries in toddlers at Baitusshalihin Applied Islamic Kindergarten. It is recommended for mothers to further increase knowledge about dental and oral health, especially rampant caries in children from an early age through print and electronic media so that they can prevent rampant caries and overcome dental health problems that occur in children.